2021
DOI: 10.3390/cells10092499
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Tissue Resident CD29-Positive Progenitor Cells in Livestock to Generate a Three-Dimensional Meat Bud

Abstract: The current process of meat production using livestock has significant effects on the global environment, including high emissions of greenhouse gases. In recent years, cultured meat has attracted attention as a way to acquire animal proteins. However, the lack of markers that isolate proliferating cells from bovine tissues and the complex structure of the meat make it difficult to culture meat in a dish. In this study, we screened 246 cell-surface antibodies by fluorescence-activated cell sorting for their ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
3
12
0
Order By: Relevance
“…First, we confirmed the cross-reactivity between cattle and antigen species based on previous reports [11][12][13], as the number of monoclonal antibodies targeting bovine antigens is limited. Notably, we used bovine muscle rather than bovine adipose to confirm crossreactivity.…”
Section: Isolation and Classification Of Aspcssupporting
confidence: 81%
“…First, we confirmed the cross-reactivity between cattle and antigen species based on previous reports [11][12][13], as the number of monoclonal antibodies targeting bovine antigens is limited. Notably, we used bovine muscle rather than bovine adipose to confirm crossreactivity.…”
Section: Isolation and Classification Of Aspcssupporting
confidence: 81%
“…A multi-color flow cytometry protocol enables to simultaneously evaluate the expression of different markers and as such to identify MSC heterogeneity [56,57]. However, there are currently no specific criteria to immunophenotype bovine MSCs, partly due to the limited availability of bovine-specific monoclonal antibodies (mAbs) or validated cross-reactive mAbs [9], as illustrated by the study of Naraoka et al Indeed, half of the tested 246 Abs showed cross-reactivity toward bovine epitopes, but 5%-10% was the highest percentage of cross-reactivity reported (for 97 Abs) while only 1%-5% cross-reactivity was reported for 17 Abs [58].…”
Section: Introductionmentioning
confidence: 99%
“…There are several commercially available cell freezing media (Yokonishi et al, 2014;Balci-Hayta et al, 2018;Fu et al, 2020;Naraoka et al, 2021). In this study, three representative media were selected to compare the effect of cryopreservation.…”
Section: Discussionmentioning
confidence: 99%
“…This is important to increase the versatility of our result by avoiding the use of specialized equipment such as a liquid nitrogen tank (Miyamoto et al, 2018). In this study, three commercially available freezing media (CB1, CB2, and LB1) were used as representative media (Yokonishi et al, 2014;Jang et al, 2017;Balci-Hayta et al, 2018;Naraoka et al, 2021). CB1 and LB1 from two different companies have been widely used to cryopreserve various kinds of mammalian cells, including bovine cells.…”
Section: E Ect Of Cell Freezing Media On Proliferation Ability Of Bov...mentioning
confidence: 99%